Ring-Opening of Oxiranes using Taeniolite-Supported Tris(Î²-Diketonato)Zirconium - Yessi Permana; Nobuyuki Ichikuni; Shogo Shimazu (Institute for Research and Community Services (LPPM) ITB, 2012)
A series of tris(Î²-diketonato)zirconium(IV) complexes was immobilized into a synthetic clay structure of Taeniolite by an ion-exchange method to generate organic/inorganic hybrid compounds. The hybrid compound served as a good catalyst for ring-opening reactions of methyl, ethyl, and dimethyl oxiranes with various alcohols to generate primary alkoxy alcohols in appreciable selectivity. This method describes a technique to immobilize cationic zirconium complexes without losing selectivity.